2015
DOI: 10.1039/c4cy01376j
|View full text |Cite
|
Sign up to set email alerts
|

Renewable fuels from biomass-derived compounds: Ru-containing hydrotalcites as catalysts for conversion of HMF to 2,5-dimethylfuran

Abstract: Ruthenium nanoparticle-containing hydrotalcite catalysts work efficiently for the conversion of biomass-derived HMF into liquid fuel 2,5-dimethylfuran.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
98
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(99 citation statements)
references
References 31 publications
1
98
0
Order By: Relevance
“…Nagpure et al. explored hydrogenolysis of HMF to DMF over Ru containing hydrotalcite(HT) catalysts and achieved complete conversion of HMF to DMF at 220 °C in 4 h . In this study, different solvents, such as protic (2‐propanol), aprotic (THF) and 1,2‐dimethoxyethane (1,2‐DME), as well as non‐polar (toluene), were explored.…”
Section: Catalytic Hydrogenation And/or Hydrogenolysis Of Biomass‐dermentioning
confidence: 99%
“…Nagpure et al. explored hydrogenolysis of HMF to DMF over Ru containing hydrotalcite(HT) catalysts and achieved complete conversion of HMF to DMF at 220 °C in 4 h . In this study, different solvents, such as protic (2‐propanol), aprotic (THF) and 1,2‐dimethoxyethane (1,2‐DME), as well as non‐polar (toluene), were explored.…”
Section: Catalytic Hydrogenation And/or Hydrogenolysis Of Biomass‐dermentioning
confidence: 99%
“…[23,35] We furthere xamined the solvent effect in the Fe-catalyzed HDO reaction (Table 2). Somep revious studies indicated that the chemicaln ature of the solvent can have as ignificant impact on the HDO of HMF to DMF.…”
Section: Solvent Effectmentioning
confidence: 99%
“…[22][23][24][25][26] In addition to the above-mentioned monometallic catalyst systems, the HDO of HMF to DMF over noble-metal-based bimetallicc atalysts has also been reported. [22][23][24][25][26] In addition to the above-mentioned monometallic catalyst systems, the HDO of HMF to DMF over noble-metal-based bimetallicc atalysts has also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The development of such iridium complexes may broaden the scope as catalysts and may act as model molecules for biological, photophysical and chemical activities , . In other words, in recent years, great attention has been focused on the conversion of biomass into valuable chemicals, in which group VIII metal complexes play a vital role , , . In particular, hydrogenation of levulinic acid to γ‐valerolactone and 1,4‐pentanediol has a significant role as a green solvent, as well as an important intermediate in several fine chemical syntheses , .…”
Section: Introductionmentioning
confidence: 99%